2021
DOI: 10.1097/pai.0000000000000928
|View full text |Cite
|
Sign up to set email alerts
|

UBE2V2 Positively Correlates With PD-L1 Expression and Confers Poor Patient Survival in Lung Adenocarcinoma

Abstract: This research aims to explore the diagnostic and prognostic value of ubiquitin-conjugating enzyme E2 variant 2 (UBE2V2) in lung adenocarcinoma (LUAD). The expression of UBE2V2 in clinical specimens was evaluated by bioinformatics analyses and immunohistochemistry. Bioinformatics analyses relying on the The Cancer Genome Atlas (TCGA) database suggested the elevated UBE2V2 mRNA levels in LUAD in comparison to adjacent normal tissues. Gene set enrichment analyses and gene ontology term enrichment analyses further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that UBE2V2 is related to the occurrence and development of various tumors. The study by Hua zhi-dan et al has shown that the expression of UBE2V2 in lung adenocarcinoma is positively correlated with PD-L 1 [21]. And the expression of UBE2V2 is negatively correlated with the severity of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that UBE2V2 is related to the occurrence and development of various tumors. The study by Hua zhi-dan et al has shown that the expression of UBE2V2 in lung adenocarcinoma is positively correlated with PD-L 1 [21]. And the expression of UBE2V2 is negatively correlated with the severity of lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 98%
“…They have sequence similarity to other ubiquitinconjugating enzymes but lack the conserved cysteine residues that are essential for the catalytic activity of E2 [19,20]. Current research shows that the protein may be closely related to the differentiation of a variety of cells [21]. In the previous screening of miRNA libraries targeting prostate cancer cells to regulate miRNAs, we found that miR-499a is significantly under-expressed in several prostate cancer cell populations, and we have also detected abnormally low expression of miR-499a in prostate cancer tissue samples.…”
Section: Introductionmentioning
confidence: 99%
“…UBE2V2 (ubiquitin-conjugating enzyme E2 variant 2) has sequence similarity to other ubiquitin-conjugating enzymes but lacks the conserved cysteine residues that are essential for the catalytic activity of E2 ( Dikshit et al, 2018 ; Zhao et al, 2018 ). Hua et al reported that UBE2V2 was identified as an independent prognostic indicator for LUAD and might function as a therapeutic target Hua et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…UBE2V2 contributes to the development and progression of many cancers, including prostate, oropharyngeal, and breast cancers, via promoting cell proliferation, suppressing cell apoptosis, and regulating immune signaling [ 71 73 ]. Moreover, UBE2V2 is an independent prognostic indicator for lung adenocarcinoma, which is closely related to the mutational processes of cigarette smoking [ 74 , 75 ]. RPS16 contributes to facilitate tumor progression of glioma via the PI3K/AKT signaling [ 76 ].…”
Section: Discussionmentioning
confidence: 99%